Genetic and Environmental Factors Are Associated with Serum 25-Hydroxyvitamin D Concentrations in Older African Americans. Issue 4 (25th February 2015) - Hansen, Joyanna G; Tang, Wenbo; Hootman, Katie C; Brannon, Patsy M; Houston, Denise K; Kritchevsky, Stephen B; Harris, Tamara B; Garcia, Melissa; Lohman, Kurt; Liu, Yongmei; de Boer, Ian H; Kestenbaum, Bryan R; et al.
Abstract: Background: Low circulating 25-hydroxyvitamin D [25(OH)D] is prevalent in African Americans, but predictors of vitamin D status are understudied compared to Caucasian populations. Objective: We investigated whether certain environmental and genetic factors are predictors of circulating 25(OH)D in 989 elderly African Americans participating in the Health, Aging, and Body Composition (Health ABC) Study. Methods: Regression analysis estimated the cross-sectional association of nongenetic (environmental) factors with 25(OH)D. Single nucleotide polymorphisms (SNPs) associated with 25(OH)D in Caucasian genome-wide association studies (GWASs) were analyzed for association with serum 25(OH)D, including analyses of all imputed SNPs in identified genomic regions. Genome-wide complex trait analysis (GCTA) evaluated the association of all (genome-wide) genotyped SNPs with serum 25(OH)D in the Health ABC Study with replication in the Multi-Ethnic Study of Atherosclerosis (MESA) cohort. Results: Gender, study site, season of blood draw, body mass index, dietary supplement use, dairy and cereal consumption, Healthy Eating Index score, and walking >180 min/wk were associated with 25(OH)D ( P < 0.05), jointly explaining 25% of the variation in circulating 25(OH)D. Multivitamin supplement use was the strongest predictor of circulating 25(OH)D, and supplement users had a 6.3-μg/L higher serum 25(OH)D concentration compared with nonusers. Previous GWAS-identified gene regions were not replicated in African Americans, but the nonsynonymous rs7041 SNP in group-specific component (vitamin D binding protein) was close to significance thresholds ( P = 0.08), and there was evidence for an interaction between this SNP and use of multivitamin supplements in relation to serum 25(OH)D concentration ( P = 0.04). Twenty-three percent (95% CI: 0%, 52%) of the variation in serum 25(OH)D was explained by total genetic variation in a pooled GCTA of 2087 Health ABC Study and MESA African-American participants, but population substructure effects could not be separated from other genetic influences. Conclusions: Modifiable dietary and lifestyle predictors of serum 25(OH)D were identified in African Americans. GCTA confirms that a proportion of 25(OH)D variability is attributable to genetic variation, but genomic regions associated with the 25(OH)D phenotype identified in prior GWASs of European Americans were not replicated in the Health ABC Study in African Americans.